2020
DOI: 10.1523/jneurosci.0894-20.2020
|View full text |Cite
|
Sign up to set email alerts
|

Chemogenetic Manipulation of Dopamine Neurons Dictates Cocaine Potency at Distal Dopamine Transporters

Abstract: The reinforcing efficacy of cocaine is largely determined by its capacity to inhibit the dopamine transporter (DAT), and emerging evidence suggests that differences in cocaine potency are linked to several symptoms of cocaine use disorder. Despite this evidence, the neural processes that govern cocaine potency in vivo remain unclear. In male rats, we used chemogenetics with intra-VTA microinfusions of the agonist clozapine-n-oxide to bidirectionally modulate dopamine neurons. Using ex vivo fast scan cyclic vol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4
1

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 101 publications
1
16
0
Order By: Relevance
“…Rats were allowed at least 10 days to recover following surgery before beginning training. At least 28 days elapsed between virus injection and the first administration of CNO or J60, allowing sufficient time for robust, persistent DREADD/reporter expression in VTA dopamine neurons (Brodnik et al, 2020;Mahler et al, 2019Mahler et al, , 2014.…”
Section: Methodsmentioning
confidence: 99%
“…Rats were allowed at least 10 days to recover following surgery before beginning training. At least 28 days elapsed between virus injection and the first administration of CNO or J60, allowing sufficient time for robust, persistent DREADD/reporter expression in VTA dopamine neurons (Brodnik et al, 2020;Mahler et al, 2019Mahler et al, , 2014.…”
Section: Methodsmentioning
confidence: 99%
“…Second, we constructed a Michaelis-Menten-like plot, of the maximum decay rate (V) found on falling transients plotted vs. [DA] o and found that both V max and K m of the best-fit curves were greater in SNCA-OVX than Snca-null mice (Figure 1F 1G,H). We explored whether the changes to DAT function might be an adaptation to, or conversely arise independently from, a deficit in evoked DA release levels in SNCA-OVX mice (Janezic et al, 2013) as chronic DA levels can impact DAT function (Calipari et al, 2013;Siciliano et al, 2018;Brodnik et al, 2020). In particular we tested whether the effect of cocaine was greater in SNCA-OVX vs. Snca-null mice in the NAc where, in contrast to dorsal striatum, there is no deficit in evoked [DA] o (Janezic et al, 2013), and found that the effect of cocaine on 1p-evoked [DA] o was similarly enhanced in NAc of SNCA-OVX mice (Supplementary Figure 1) indicating that altered DAT function in SNCA-OVX mice occurs is not due to a DA release deficit.…”
Section: Dat Function Is Potentiated By α-Synucleinmentioning
confidence: 99%
“…Baseline DA uptake was determined by setting K m values to 0.18 μM and all cocaine-induced alterations in uptake were attributed to changes in apparent K m . Inhibition constants ( K i ) were determined to calculate the necessary cocaine concentration to produce 50% DA uptake inhibition and were then calculated using the equation K m /slope [ 17 , 31 , 38 , 39 ]. Demon Voltammetry and Analysis software [ 29 ] was used for all acquisition and analysis of FSCV data.…”
Section: Methodsmentioning
confidence: 99%